Is Iceland’s equal pay management system fair to employees? : an Icelandic municipality case study - Sigríður Elín Sveinsdóttir 1983- (2019)
Employees’ perceptions of fairness in the workplace significantly impacts their behavior outcomes and attitudes, which clearly influences organizational success. The goal of this case study is to explore the overall fairness of the equal pay management system (EPMS) and what influences employees’ perception of the justice of this system. In this study, was explored the relationship between organizational justice dimensions and key employee behavioral outcomes; job satisfaction, organizational commitment and turnover. As well as explore whether or not genders perception of justice affects theses outcomes. A quantitative research method was used in this research project; the main data collecting tool was self-complete questionnaires. The survey was submitted to employees of a typical municipality in Iceland and it contained 52 close-ended questions, most measured on five-point Liker scale. The results of this case study show that employees ´perception of overall fairness of the equal pay management system is high and that there is no significant difference between genders. Employee attitudes regarding the equal pay management system and gender equality were very positive. Women perceived less distributive justice than men, but this was because they had less managerial responsibility and less authority to take wage decisions. Increased managerial responsibility was associated with higher procedural and informational justice. The relationship between organizational justice of the equal pay management system and behavioral outcomes job satisfaction and organizational commitment is positively correlated, however the relationship is negatively correlated to turnover intention. Gender does not alter the effect of perceived justice on job satisfaction, organizational commitment and turnover intention.Key words: Organizational Justice, Overall Fairness, Equal Pay Certificate, Equal Pay Management System, Gender Pay Gap, Human Resource Management, Organizational Psychology Hvernig starfsmenn upplifa sanngirni innan ...